SPREAD SIMULATION OF CARBON MONOXIDE (CO) UNDER THE PASUPATI FLYOVER TAMAN JOMBLO USING COMPUTATIONAL FLUID DYNAMICS (CFD) SIMULATION - MAULA ALFIANTO (NIM: 12811012); Pembimbing: Dra. Atika Lubis, MS., LUTHFIE
In the rapid development in major cities of Indonesia, air pollution is a major problem that often occurs. The largest source of urban air pollution is caused by motor vehicle activity. Bandung city which is one of the areas with the highest traffic in Indonesia built a park named Taman Jomblo that taking place right under the Pasupati Flyover. The park is flanked by the entrance and exit Pasupati Flyover, and also Taman Sari street. With the size of 22.3 m x 34.5 m x 7 m, then the whole area of the park will be affected by air pollution from the roads that flanking. The information about air quality in the park becomes important. This study simulated the spread of carbon monoxide (CO) in the Taman Jomblo using the model of air flow computational fluid dynamics (CFD). The turbulence flow was performed by Fluent software using k-epsilon equation. The simulations run on the time schemes with the different condition of the volume of motor vehicles. The results show that there are three schemes that have the CO emission greater than 10 ppm that is above the threshold set by the KLH. It were weekdays – morning scheme, Friday – noon scheme, and Friday – afternoon scheme.